Between areolated and band-shaped spots: a revision of Lacronia Strand, 1942 (Opiliones, Gonyleptidae). - Carvalho, Rafael N.; Kury, Adriano B. (European Journal of Taxonomy, 2023)
The genus Lacronia Strand, 1942 is herein revised, and a maximum parsimony phylogenetic analysis of morphological characters (30 taxa, 115 characters, 2962 scorings) is performed to test its monophyly. As a result, Lacronia is herein made monophyletic by means of the inclusion of Discocyrtus boraceae B. Soares, 1942, Discocyrtus niger Mello-Leitão, 1923 and Discocyrtus tenuis Roewer, 1917. Lacronia including those species is the sister group of Discocyrtus s. str. inside the DRMN-clade, and should be removed from Pachylinae Sørensen, 1884, although without a new subfamilial assignment for now. Four new junior subjective synonyms are detected for the first time (Discocyrtus rarus B. Soares, 1944 = Discocyrtus fazi Piza, 1942 = Discocyrtus niger Mello-Leitão, 1923; Discocyrtus infelix Mello-Leitão, 1940 = Discocyrtus nigrolineatus Mello-Leitão, 1923 = Discocyrtus tenuis Roewer, 1917). Accordingly, the following new combinations are proposed: Lacronia boraceae (B. Soares, 1942) comb. nov., Lacronia nigra (Mello-Leitão, 1923) comb. nov. and Lacronia tenuis (B. Soares, 1942) comb. nov. Lacronia is endemic to the Atlantic province of Brazil, with verified records from the states of Rio de Janeiro, Santa Catarina and São Paulo. As a geographic note, the record of ‘D. fazi’ for Chile is here discussed and considered incorrect.